Long-term efficacy and safety of anticoagulation after atrial ﬁbrillation ablation: data from the JACRE registry. Issue 3 (March 2021) - Inoue, Koichi; Hirao, Kenzo; Kumagai, Koichiro; Kimura, Masaomi; Miyauchi, Yasushi; Tsushima, Eiki; Ohishi, Mitsuru; Kimura, Kazumi; Yasaka, Masahiro; Yamaji, Hirosuke; Okawa, Keisuke; Fujimoto, Manabu; et al.
Highlights: Thromboembolism was rare in patients with atrial fibrillation treated with catheter ablation (CA). Major bleeding was not rare in those patients. Discontinuation of oral anticoagulants (OACs) after CA was not a significant risk for stroke. Continuing OACs was rather associated with increased bleeding risk. Discontinuation of OACs is an important option after successful CA. Abstract: Background: Catheter ablation (CA) is an important strategy for managing atrial fibrillation (AF). However, long-term anticoagulation strategies and clinical outcomes following CA, including thromboembolism and bleeding, have not yet been elucidated. Methods: We established a prospective registry, called the JACRE registry, for patients on rivaroxaban or warfarin administration who received CA for AF. The outcomes up to 30 days following the procedure were reported previously. The present study involved longer follow-up of patients enrolled in this registry to evaluate long-term anticoagulation strategies and clinical outcomes. Results: Data of 975 patients (rivaroxaban, n = 823; warfarin, n = 152) were collected from 27 institutes. Patient population had mean age 63.7 ± 10.3 years, 710 (72.8%) males, mean CHA2 DS2 -VASc score 1.9 ± 1.5, and mean follow-up period 28.7 ± 12.7 months after the index procedure. Anticoagulants were continued in 496 (50.9%) patients during the follow-up. Thromboembolism occurred in 3 patients, hemorrhagic stroke in 5, and major bleeding events in 9 (annualized event rate, 0.13%, 0.22%, and 0.40% per patient-year, respectively). There were no differences in the composite event rate of thromboembolism and International Society on Thrombosis and Haemostasis major bleeding between rivaroxaban and warfarin cohorts (0.53% and 0.55% per patient-year, respectively). Conclusions: Long-term incidence of thromboembolism was extremely low in patients with AF treated with CA, while that of major bleeding was not especially low. Clinical Trials Registry: UMIN000032829 / UMIN000032830